Labeling PKI dan Dampaknya Terhadap Pemenuhan HAM Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa - Ceprudin Ceprudin; Retno Mawarini Sukmariningsih (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2024)
This study aimed to counter the narrative that has already spread wildly in the wider community that believers of unofficial religion (penghayat kepercayaan) to God Almighty (hereinafter written Belief) were identical to communist. This writing is important to reveal the real facts about the struggle around 1965 and its excesses against the existence of believers of unofficial religion (penghayat kepercayaan) in Indonesia. Even though decades have passed, the labeling as communist and non-religion, which was then followed by the misguided and deviated stigma until now it hasn't disappeared. For the groups of “penghayat kepercayaan”, this condition has left a deep trauma. Even though the government has issued a series of laws and regulations that sought to protect and fulfill the groups of “penghayat kepercayaan”, but it has not been able to completely cleared up the stigma of “non religion people - communist” which has widespread in society. This period was be recognized by “penghayat kepercayaan” was the toughest period in the Indonesian history. The label of communist made the “penghayat kepercayaan” fell out and not a few organizations of “penghayat kepercayaan” were be